A Simple Method of Electrospun Tungsten Trioxide Nanofibers with Enhanced Visible-Light Photocatalytic Activity - Ofori, Frank Agyemang; Sheikh, Faheem A.; Appiah-Ntiamoah, Richard; Yang, Xinsheng; Kim, Hern (Nano-Micro Letters, 2015)
The present study involves the fabrication of tungsten trioxide (WO3) nanofibers by an electrospinning technique using polyvinyl pyrrolidone (PVP)/citric acid/tungstic acid as precursor solution. It was found that the PVP concentration was one of the most crucial processing parameters determining the final properties of WO3 nanofibers. The optimum concentration of PVP was from 75 to 94 g L−1. The average diameter of the nanofibers increases with increasing the PVP concentration, whereas it is decreased after sintering and orthorhombic structure were formed at 500 °C. The photocatalytic properties of the as-synthesized nanofibers were also investigated by degrading methylene blue and twofold efficiency was obtained compared with that of commercial WO3 microparticles.